On R-unipotent semigroups with ΠL1-embeddable band of idempotents - Billhardt B. (2017)
© 2015, Springer Science+Business Media New York. Let ΠL 1 denote a direct power of L 1 , the two-element left zero semigroup with identity adjoined. We prove that the semigroups in the title are embeddable into transformation semigroups which naturally generalize the Vagner one-point completion of the symmetric inverse semigroup. We give some examples and show that our representation provides a convenient way to construct E-unitary covers and embeddings of E-unitary such semigroups into semidirect products of ΠL 1 -embeddable bands by groups.